The The Correlation between Body Mass Index and Plantar Fasciitis Pain Age 20-50 years old - Robi Sutanto; Nuryani Sidarta (Jurnal Biomedika dan Kesehatan, 2022)
BACKGROUND Plantar fasciitis is one of the most common causes of pain in the heel area in adults. This condition is an inflammation that occurs due to microtrauma that occurs repeatedly. The pain that appears is usually most felt when you first get up in the morning, or after resting on both legs for a long time. Body mass index (BMI) is one of the factors that can contribute to the onset of plantar fasciitis. However, until now there are still pros and cons of opinions regarding the role of the BMI. This study aims to see the relationship between these two variables with plantar fasciitis. METHOD This study is an analytical study conducted with a cross-sectional approach to see the relationship between Body Mass Index and the incidence of plantar fasciitis. The data taken is secondary data from a private hospital in the Tangerang area with a time period between August and October 2021. The data were analyzed using Fisher's exact test with a significance limit of < 0.05. RESULT A total of 68 subject data from medical records at Siloam Hospital Lippo Village were taken in this study. Based on the study, it was found that 81.1% of people with excessive BMI and plantar fasciitis and the highest age distribution were in the range of 30-50 years and most were found in the female sex. Statistical analysis showed that there was a relationship between body mass index and plantar fasciitis pain aged 20-50 years (P=0.049) CONCLUSION Based on the results of the study, there was a relationship between body mass index and plantar fasciitis pain between the ages of 20-50 years. Key Words: Plantar fasciitis, Fascia Plantaris, Heels Pain, Body Mass Indeks